2018
DOI: 10.1002/cpph.37
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution and Electrophysiological Characterization of Ion Channels in Lipid Bilayers

Abstract: Detergent-solubilized purified ion channels can be reconstituted into lipid bilayers for electrophysiological analysis. Traditionally, ion channels were inserted into vesicles and subsequently fused with planar "black lipid membranes" formed from lipids dissolved in a hydrophobic solvent such as decane. Provided in this article is a step-by-step guide to reconstitute purified ion channel proteins into giant unilamellar vesicles (GUVs). This procedure results in the formation of proteoliposomes that can be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Single channel ion conductance was measured in lipid bilayers using an Orbit Mini workstation (Nanion Technologies, München, Germany) with 50 μm MECA4 recording chips with 4 microelectrode cavities (Ionera Technologies, Freiburg, Germany) as previously described [46]. Voltage was controlled by the EDR 3 software (Elements, Cesena, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Single channel ion conductance was measured in lipid bilayers using an Orbit Mini workstation (Nanion Technologies, München, Germany) with 50 μm MECA4 recording chips with 4 microelectrode cavities (Ionera Technologies, Freiburg, Germany) as previously described [46]. Voltage was controlled by the EDR 3 software (Elements, Cesena, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…In the conventional artificial lipid bilayer recording technique, it takes several tens of minutes or several hours to measure channel currents because it takes a long time to both make the lipid bilayer membrane (several minutes or more) and incorporate the ion channels into the membrane (from approximately ten minutes to several hours) although it depends on the type of channel. In addition, for a commercially available system to measure channel current in the artificial membrane using giant unilamellar vesicles, it has been reported that average recording times are 1-3 times per day 33 . Our system provides much higher measurement efficiency than the other techniques.…”
Section: Use Of Gold Probes Comprising a Hydrophobic Layer Results In...mentioning
confidence: 99%
“…GUVs made of POPC:POPG (1:1) lipids were prepared by the electroformation method [ 26 , 27 ]. Fluorescently labelled lipids (FLLs) were used to stain the membrane of GUVs to perform the vesicle fusion assays.…”
Section: Methodsmentioning
confidence: 99%